Oral rehydration therapy : a community trial comparing the acceptability of homemade sucrose and cereal-based solutions - Chowdhury, AMR; Karim, F.; Rohde, J.E.; Ahmed, J.; Abed, F.H. (Bulletin of the World Health Organization, 2019)
Sugar-based oral rehydration therapy (ORT) for diarrhoea is promoted in many countries of the world. One programme in Bangladesh has instructed more than 13 million mothers in the preparation of a sugar-salt solution in the home; despite very high rates of correct mixing and knowledge, subsequent application was found in only some 20% of all diarrhoea episodes. Since rice is far more available in rural homes (95%) than any type of sugar (30%) and rice gruel is a widely accepted food during illness, a field trial was conducted in three areas (total population, 68,345) to compare the acceptability and use of rice-based ORT with that of sugar-based ORT. Although the mothers unanimously agreed that the rice-based solutions "stopped" the diarrhoea more quickly, they used the sugar-based solutions twice as often (in 40% of severe watery episodes) as the rice-based solutions (in 18%), because the rice-ORT was much more time-consuming and difficult to prepare. The observed reduced utilization of home-made rice-ORT makes it a poor substitute for sugar-ORT at the community level in rural Bangladesh. PIP: